On the depolarization of bodies invariant under a rotation. - Monzon, J.C (IEEE Transactions on antennas and propagation)
It is shown that a body of arbitrary material constitution, but invariant under a fixed rotation, must be periodic and will not monostatically depolarize under linear polarization axial incidence if reciprocal, unless the body is invariant under a rotation by 180°. For circular polarization, the result is more general, the body will not depolarize even if it is not reciprocal. Forward scattering and other considerations are also included. The theory is illustrated by application to a few selected scatterers